Commercial Impracticability under the Indian Law of Contract: The UNIDROIT Principles as the Way Forward? - Saloni Khanderia (UCL Journal of Law and Jurisprudence, 2018)
The present era of heightened liberalisation has encouraged an increasing number of jurisdictions across the globe to offer some respite to the parties to a contract when they experience a subsequent and unforeseen change in circumstance in the form of hardship. However, there is sufficient judicial dicta in India – a common law jurisdiction – to detect a certain hostility to recognising any such situation that is short of impossibility within the definition of section 56 of the Indian Contract Act 1872. The blind application of traditional common law principles has proven to be unsuitable to resolving the predicaments arising in modern-day contracts, which are often affected by inflation and other legal or political changes that have the potential to alter the contracted price of performance to the detriment of one party. The present author suggests that the Indian courts should begin to refer to the International Institute for the Unification of Private Law’s (UNIDROIT) approach espoused in its Principles on International Commercial Contracts (the UPICC). Unlike the Indian law of contract, the UPICC adopts a dichotomy between the theories of hardship and force majeure, and consequently provides different solutions to address these matters. Employing the UPICC as a gap-filler will assist the Indian courts in interpreting these issues according to well-defined and internationally accepted standards so that the parties can receive fair and adequate relief when the performance of their contract has been affected by hardship. For full text, please click here
Keywords: UNIDROIT Principles on International Commercial Contracts.; India; the law of contract; performance; impossibility; hardship